Rekonstruksi Bisma di dalam Cerpen “Bisma” Karya Putu Wijaya - Sudewa, I Ketut (Humanis, 2025)
The character of Bhishma in the Mahabharata wayang tradition is known as a central figure who ultimately causes the downfall of the Kingdom of Hastinapura. Putu Wijaya reconstructs this character in his short story “Bisma” by blending imagination with the social realities of contemporary Indonesian society. Bhishma’s greatness and controversy are reimagined through Putu Wijaya’s distinctive style, which reflects the current social conditions. This reconstruction gives rise to a ‘new’ Bhishma—one that resonates with today’s readers. This study aims to examine how the character of Bhishma is reinterpreted within the modern Indonesian social context through a sociological approach to literature. The method used is library research, employing reading, observation, note-taking, and interpretive techniques. The findings reveal that Bhishma is portrayed as both an imaginative figure and a societal idol, particularly for the urban community of Jakarta, reflecting the contemporary need for role models amidst ongoing social dynamics.